2006
DOI: 10.1007/s00705-006-0734-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of type-specific and cross-reactive neutralizing conformational epitopes on the major capsid protein of human papillomavirus type 31

Abstract: The majority of the neutralizing epitopes of papillomaviruses (PV) are conformation-specific and have not been fully characterised. Studies have, to date, been limited to a few HPV types only. We analysed the epitopes on the major capsid protein (L1) of Human papillomavirus (HPV) type 31 using monoclonal antibodies (MAbs) generated against HPV-31 virus-like particles (VLPs). The type-specific MAbs against HPV-31 were all found to be neutralizing and recognized conformation-dependent epitopes. Two other MAbs di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 46 publications
1
30
0
3
Order By: Relevance
“…Protection is mediated by neutralizing antibodies, and the work of several laboratories has identified cross-neutralizing epitopes (10)(11)(12)(13)(14)(15)(16)(17)(18). We have previously reported that monoclonal antibody RG-1, which is specific for residues 17-36 of L2 from HPV16, neutral-izes both HPV16 and HPV18 and protects naïve mice from challenge with HPV16 (12).…”
mentioning
confidence: 99%
“…Protection is mediated by neutralizing antibodies, and the work of several laboratories has identified cross-neutralizing epitopes (10)(11)(12)(13)(14)(15)(16)(17)(18). We have previously reported that monoclonal antibody RG-1, which is specific for residues 17-36 of L2 from HPV16, neutral-izes both HPV16 and HPV18 and protects naïve mice from challenge with HPV16 (12).…”
mentioning
confidence: 99%
“…HPV31 L1 MAbs against immunogens representing the HPV31 reference sequence (GenBank accession number J04353) were previously generated (39). The majority of MAbs were raised against L1L2 VLPs; the exceptions were MAbs 31.D24 and 31.A19, where L1 VLP immunogens were used.…”
Section: Resultsmentioning
confidence: 99%
“…*, P Ͻ 0.05; **, P Ͻ 0.01; NS, no significant difference (P Ͼ 0.05). a Epitope location, structure (C, conformational; L, linear), specificity (TS, type specific; XR, cross-reactive), and MAb neutralizing potential were taken from the work of Fleury et al (39). -, MAbs for which binding or neutralization concentrations could not be determined at the highest input concentrations (by ELISA, 250 g/ml for all MAbs except 31.D24, for which the highest input concentration was 20 g/ml, and by neutralization assay, 125 g/ml for all MAbs except 31.D24, for which the highest input concentration was 10 g/ml).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rim of the pentamer pocket is extremely variable contrary to its floor. With a few exceptions, all HPV-neutralizing monoclonal antibodies analyzed so far are type-specific and recognize conformational epitopes within these surface-exposed hyper variable loops (Pastrana et al, 2004;Fleury et al, 2006). HPV16 and HPV11 VLPs epitopes recognized by neutralizing mAbs are shown on Fig.…”
Section: Introductionmentioning
confidence: 99%